Praktik Inovasi Pendidikan Karakter pada Siswa Sekolah Dasar Melalui Program Salam Literasi di SDN Sindangbarang 04 Karangpucung Cilacap - Oktafiani, Maulida; Fajar, Wildan Nurul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the implementation of the SALAM LITERASI (One Child Fifteen Minutes of Reading) Program and its impact on strengthening student character at SDN Sindangbarang 04 Karangpucung, Cilacap. This program integrates 15 minutes of reading before learning, filling out a literacy journal, and SALAM BERBAGI activities as literacy habits that support character building. The study used a qualitative descriptive approach with research subjects consisting of the principal, class teachers, students, and parents who were selected purposively. Data were collected through observation, interviews, documentation, and student reflection questionnaires, then analyzed using the Miles, Huberman, and Saldaña model which includes data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the SALAM LITERASI Program contributed to strengthening the character of discipline, responsibility, independence, curiosity, and communication. This program also encouraged increased student involvement in literacy activities, formed sustainable reading habits, and strengthened literacy culture through reflection activities and sharing reading experiences. Program implementation was supported by teacher consistency, school support, and parental involvement. Research findings show that the SALAM LITERASI Program has the potential to be an alternative literacy habit that supports strengthening student character in elementary schools.